Implementasi Metode Certainty Factor pada Sistem Pakar Berbasis Web untuk Diagnosis Gangguan Kesehatan Reproduksi Pria - Endwin Levis Putra Zendrato; Kecitaan Harefa (CV. Multi Kreasi Media, 2026)
Male reproductive health disorders are among the health problems that can significantly affect quality of life, sexual function, and fertility. Limited public knowledge, reluctance to seek medical consultation due to embarrassment, and restricted access to healthcare services often lead to delayed diagnosis and treatment. This study aims to develop a web-based expert system using the Certainty Factor method to support the early diagnosis of male reproductive health disorders at Pandawa Main Clinic. The research was conducted through literature review, observation, and interviews with an andrology specialist to obtain data on diseases, symptoms, diagnostic rules, and confidence values. The system was developed using the PHP programming language with the Laravel framework and MySQL as the database management system. The Certainty Factor method was applied to calculate the confidence level of a diagnosis based on the symptoms selected by users. The system provides information on the identified disease, the confidence percentage of the diagnosis, and recommendations for initial treatment. Functional testing using the Black Box Testing method demonstrated that all system features operated according to the specified requirements. The results indicate that the developed expert system is capable of assisting users in obtaining early diagnostic information quickly, conveniently, and through online access, while also supporting healthcare professionals during the initial consultation process. This system is intended to serve as a decision-support tool and does not replace the final diagnosis or treatment provided by an andrology specialist.